Le mot et l’image dans la sémiotique lithuanienne - Kęstutis Nastopka (Signata, 2019)
This paper gives an overview of major publications of the Lithuanian semioticians who analyze the relationship between the word and the image within the framework of Algirdas Greimas’ general theory of meaning. I include my own analysis of the relationship between verbal and visual discourse, based on the periphrasis of the evangelical story of Emmaus in the poem The travellers of Emmmaus (1946) by Alfonsas Nyka-Niliūnas, and in the painting “Dinner in Emmaus” (1967) by Vincas Kisarauskas. In Nyka-Niliūnas’ poem, mundane life is contemplated within the range of God’s kingdom.Lithuanian semioticians have also investigated a variety of visual objects in semiotic terms. Gintautė Žemaitytė (2011) analyzes the plastic and figurative levels of the “Lavazza” coffee advertising campaign and concludes that it is an example of aesthesis when the object overwhelms and assimilates the subject. Dainius Vaitiekūnas, in his book “Lithuanian literature and advertising: poetry of consumer society” (2014), reveals the values of consumer society by analyzing verbal discourses of prose and poetry, as well as visual products such as logos and trademarks. Edvardas Kavarskas, designer of the prestigious packaging of Lithuanian vodka, in the journal Semiotika (2016) (www.semiotika.lt), discusses the range of meanings emanating from the object. Jovita Bružienė, in the same journal (2013), analyzes the 1613 map of the Grand Duchy of Lithuania and links the visual figures of the map with the narrative transitions between different spatial modes. The author’s synoptic gaze focuses on the plastic composition of the map and distinguishes certain topological oppositions such as quadriangle/circle, vertical/horizontal line, center/periphery. In her doctoral thesis “Narrative strategies in Šarūnas Sauka’s paintings” (2013), Monika Saukaitė reconstructs the simulacrum of enunciation in the visual discourse and looks at how it integrates the addressee of the enunciation into the structure of the painting.In the analysis of visual discourse, Lithuanian semioticians draw mainly on the work of Greimas and Jean-Marie Floch, as well as Youri Lotman’s cultural semiotics. Hence our special interest in issues of cultural heritage. In Lithuania, visual semiotics is developed in parallel with literary semiotics.